Chapter 6 The user-friendly Galen Ḥunayn ibn Isḥāq and the adaptation of Greek medicine for a new audience - Vagelpohl, Uwe (Taylor & Francis, 2018)
When a text is translated into another language and leaves its previous linguistic, cultural and social context, it also leaves its old audience behind. The new audience the text now faces has its own set of requirements, which may only partly overlap with those of the original audience. The task of bridging the gap between old and new audiences and appealing to the latter falls to the translator. In the field of medieval Arabic medicine, an abundance of extant medical translations allows us to document how translators attempted to appeal to their audience and how they took the immediate practical needs of their readers into account. This chapter presents samples from this material and illustrates the insights it can provide into the relationship between the translator and his audience.